WNT Ligand Dependencies in Pancreatic Cancer - Aguilera, Kristina Y.; Dawson, David W. (Frontiers in Cell and Developmental Biology, 2021)
WNT signaling promotes the initiation and progression of pancreatic ductal adenocarcinoma (PDAC) through wide-ranging effects on cellular proliferation, survival, differentiation, stemness, and tumor microenvironment. Of therapeutic interest is a genetically defined subset of PDAC known to have increased WNT/β-catenin transcriptional activity, growth dependency on WNT ligand signaling, and response to pharmacologic inhibitors of the WNT pathway. Here we review mechanisms underlying WNT ligand addiction in pancreatic tumorigenesis, as well as the potential utility of therapeutic approaches that functionally antagonize WNT ligand secretion or FZD receptor binding.